VIRUS AS A CAUSE OF SALIVARY GLAND DISEASES - Etis Duhita Rahayuningtyas; Riani Setiadhi (Odonto : Dental Journal, 2019)
Background: Enlargement in the extraoral region with the absence of abnormal dental and periodontal structures are sometimes seen in dental practice, sometimes followed by xerostomia. Enlargement of the acute nonsuppurative salivary glands has been associated with several types of viruses. The purpose of this paper is to review salivary gland diseases associated with non-HIV and HIV viral infections.Discussion: Non-HIV viruses which were detected in the salivary glands including Paramyxovirus, cytomegalovirus (CMV), Hepatitis C virus (HCV), human papilloma viruses (HPV), Epstein-Barr virus (EBV), human herpes simplex virus (HHSV-8), and coxsackie virus. HIV-associated salivary gland disease typically presents with xerostomia and/or intraglandular lymph nodes, and diffuse infiltrative lymphocytosis syndrome (DILS). The most common viral infection conditions in salivary gland disorders are mumps and HIV. Enlargement and inflammation of the glandular structures will affects the control of salivary secretion by nerves. Parasympathetic nerves block conducted signals to the salivary glands, so the salivary flow isdecreased.Conclusion: There is association between viral infection and diseases of thesalivary gland. By knowing sequelae viruses on the salivary gland, dentists are expected to understand the clinical condition and therapeutic that should be given to the patients.